Quantification of Earth Material for Sustainable Road Works in Southeast Nigeria - Nwamgbowo, Paschal; Nnadi , Ezekiel; Eze, Val Hyginus Udoka; Kibwami, Nathan (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
This paper examines the use of earth materials in sustainable road construction in South East, Nigeria. The study aims to determine factors associated with the use of earth materials, identify limiting factors, and examine strategies to improve their use. The study population comprised 60 engineers and craftsmen using local materials. The results show limitations in the use of earth materials in sustainable road works. The study recommends contracting firms to develop better storage facilities for earth materials to prevent damage and wastage. It also suggests incorporating earth materials into construction education curriculums to sensitize students to their potential benefits. The government should adopt a policy of adapting earth materials that require minimal capital and foreign exchange and utilizing available raw materials and skills in small-scale operations. The study's findings highlight the importance of sustainable road construction in Nigeria's socio-economic growth.